A Passive Battery Management System for Lead-Acid battery - Pop Adrian Augustin; Inte Razvan; Oprea Claudiu; Ruba Mircea (EPJ Web of Conferences)
One of the dangerous issues that can appear when working with batteries is the imbalance of the cell. To overcome this problem, the battery management systems (BMS) can provide balancing by extracting or adding charge according to the needs. The goal is to protect the battery from dangerous overheating or damage but also to prolong the battery’s lifetime. Without a BMS the individual cell voltage will drift away, and the estimation of the state of charge will be unreal. The BMS is detecting automatically when the battery pack is charged, and it enables passive balancing of charged cells. The goal of this paper is to test the BMS system adapted for lead acid batteries and visualizing the performances by using real time application by means of graphical instruments. The measured parameters as current, voltage, temperature is displayed with the help of dSPACE and Typhon HIL platforms.